Resident Innate Immune Cells in the Cornea - Liu, Jun; Li, Zhijie (Frontiers in Immunology, 2021)
The cornea is a special interface between the internal ocular tissue and the external environment that provides a powerful chemical, physical, and biological barrier against the invasion of harmful substances and pathogenic microbes. This protective effect is determined by the unique anatomical structure and cellular composition of the cornea, especially its locally resident innate immune cells, such as Langerhans cells, mast cells, macrophages, γδ T lymphocytes, and innate lymphoid cells. Recent studies have demonstrated the importance of these immune cells in terms of producing different cytokines and growth factors, in corneal homeostasis, and pathologic conditions. This review paper briefly describes the latest information on these resident immune cells by specifically analyzing research from our laboratory.